Promoting Climate-Resilient Farming Practices in Flood- and Drought-Prone Communities - Ahmad, Farhan (Jurnal Hexagro, 2026)
Climate change poses a growing risk to agriculture-dependent livelihoods in northern Pakistan due to unpredictable rainfall, flooding, droughts, and heightened pest challenges. A Climate-Resilient Agriculture (CRA) capacity-building initiative was carried out in the Districts of Buner and Shangla under the Resilient Recovery and Adaptation Project (RRAP), supported by UNDP. This article records the design, execution, and results of community-driven CRA sessions led by Islamic Relief Pakistan (IRP) Agriculture Officers. Through participatory training, the initiative introduced climate-smart agricultural practices, soil and water conservation, integrated pest management, and livelihood diversification. Quantitative participation data and qualitative responses suggest significant community involvement and a strong willingness to implement practices such as mulching, crop diversification, and efficient irrigation. Despite challenges such as limited access to robust seeds and compromised irrigation systems, the program improved farmers' resilience and risk awareness. The results highlight the success of targeted, affordable CRA strategies in enhancing resilience in at-risk agricultural families.